The Increased Risk of Thyroid Cancer-Specific Mortality With Tumor Size in Stage IVB Patients - Zhang, Junyi; Cheng, Xiaoyun; Su, Bin; Wang, Xingchun; Wang, Lu; Jayachandran, Muthukumaran; Sun, Xiaoting; Bu, Le; Huang, Yueye; Qu, Shen (Frontiers in Oncology, 2020)
Purpose To investigate the risk-stratifying utility of tumor size and a threshold for further stratification on cancer-specific mortality of thyroid cancer (TC) patients in stage IVB. Methods 1,345 patients (620 males and 725 females) with initial distant metastasis over 55 years between 2004 and 2016 from Surveillance, Epidemiology, and End Results database were investigated, with a median follow-up time of 23 months [interquartile range (IQR), 5–56 months] and a median age of 70 years (IQR, 63–77 years). TC-specific mortality rates were calculated under different classifications. Cox regressions were used to calculate hazard ratios (HRs) and Kaplan-Meier Analyses were conducted to investigate TC-specific survivals. Results In the whole cohort, patients with tumors >4cm had the highest TC-specific mortality (67.9%, 330/486), followed by tumor size >1cm but ≤4cm (43.08%, 190/441), and tumor size ≤1cm (32.69%, 34/104). Kaplan-Meier curves showed the increased tumor size was associated with a statistically significant decrease in TC-specific survival (P<0.001). Papillary thyroid cancer (PTC) patients with tumors >4cm had significantly higher hazard ratios (HRs) of 2.84 (1.72 to 4.70) and 3.11 (1.84 to 5.26) after adjusting age, gender, race, and radiation treatment, compared with patients with tumors ≤1cm (P<0.001). The TC-specific mortalities and survivals were further investigated among more detailed subgroups divided by different tumor size, and a threshold of 3cm could be observed (P<0.005) for risk stratification. Conclusions Mortality risk increased with tumor size in PTC patients in stage IVB. Our findings demonstrated the possibility of further stratification in IVB stage in current TNM staging system. Patients with tumor size over 3cm had an excessively high risk of PTC-specific mortality, which may justify the necessity of more aggressive treatment for them.